Experimental analysis of benzene derivative adsorption in single and binary systems using activated carbon. (2015) - Iovino, Pasquale; Erto, Alessandro; Capasso, Sante; Natale, Michele Di; Canzano, Silvana; Lama, Annalisa; Musmarra, Dino
This work is an experimental analysis of o-xylene and ethylbenzene adsorption onto a commercial activated carbon in both single-compound and binary systems. The effect of temperature and salinity was assessed for single-compound systems, confirming that the adsorption of these analytes is an exothermic phenomenon occurring in active sites other than those where ionic substances are adsorbed. The estimate of the isosteric heat of adsorption allowed demonstrating that there are no lateral interactions between o-xylene and ethylbenzene molecules and that the Langmuir model can be used for data interpretation. Adsorption tests in binary systems showed that o-xylene adsorption is affected by the presence of ethylbenzene, while the adsorption capacity of ethylbenzene remains unchanged in both single-compound and binary systems. Finally, based on a modelling analysis of the binary systems, the Langmuir multicomponent model appears to be a statistically reliable tool for o-xylene binary data prediction, while the Langmuir single-compound model is suitable for the prediction of ethylbenzene binary data, in line with the experimental evidence showing the absence of any competition phenomena.